NIR–vis–UV Light‐Responsive High Stress‐Generating Polymer Actuators with a Reduced Creep Rate. Issue 14 (3rd May 2021) - Pan, Xinglong; Verpaalen, Rob C. P.; Zhang, Huiyi; Debije, Michael G.; Engels, Tom A. P.; Bastiaansen, Cees W. M.; Schenning, Albert P. H. J.
Abstract: Untethered, light‐responsive, high‐stress‐generating actuators based on widely‐used commercial polymers are appealing for applications in soft robotics. However, the construction of actuators that are stable and reversibly responsive to low‐intensity ultraviolet, visible, and infrared lights remains challenging. Here, transparent, stress‐generating actuators are reported based on ultradrawn, ultrahigh molecular weight polyethylene films. The composite films have different draw ratios (30, 70, and 100) and contain a small amount of graphene in combination with ultraviolet and near‐infrared‐absorbing dyes. The composite actuators respond rapidly ( t 0.9 < 0.8 s) to different wavelengths of light (i.e., 780, 455, and 365 nm). A maximum photoinduced stress of 35 MPa is achieved at a draw ratio of 70 under near‐infrared light irradiation. The photoinduced stress increases linearly with the light intensity, indicating the transfer of light into thermally induced mechanical contraction. Moreover, the addition of additives lead to a reduction in the plastic creep rate of the drawn films compared to their nonmodified counterparts. Abstract : Transparent and stress‐generating NIR–vis–UV light‐responsive actuators based on ultradrawn, ultrahigh molecular weight polyethylene composite films including graphene in combination with a UV and NIR dye are fabricated. Such composite films can respond rapidly (<0.8 s) to different wavelengths of light with a maximum photoinduced stress of 35 MPa.